Analisis Kontribusi Human Error terhadap Kecelakaan Lalu Lintas di Bali: Pendekatan Mixed-Method dengan Desain Triangulasi Konvergen - Mardikawati, Budi; Mulyaningtyas, Dinda One; Fitasari, Yusime (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
This study aims to analyze the contribution of human error factors to traffic accidents in Bali using a mixed-method approach with a convergent triangulation design. Data were collected from three main sources: traffic accident records from the Bali Regional Police for the 2023–2024 period, a survey of 166 respondents, and in-depth interviews with five road safety experts. Quantitative analysis was conducted through statistical descriptions, Incident Rate per Million Vehicle Kilometers (IRMS), and assessment of public understanding levels, while qualitative analysis was carried out using a thematic approach supported by ChatGPT software. The results show that the majority of accidents occurred in Denpasar, with victims predominantly in the young adult age group (20–29 years), with senior high school education or equivalent, and without a driver's license. The most common type of accident was single-vehicle crashes involving motorcycles, occurring on collector roads in the afternoon, under clear weather and good road conditions. The survey revealed that only 3 out of 9 aspects were well understood by most respondents, indicating the need for public outreach regarding age, occupation, driver behavior, road conditions, road geometry, and weather. Expert interviews emphasized the importance of education through direct outreach, mass media, improved infrastructure, and stricter law enforcement. This study highlights the need for systemic and educational interventions to reduce the contribution of human error to traffic accidents in Bali.